Probiotic Properties of Lactobacillus paracasei subsp. paracasei L1 and Its Growth Performance-Promotion in Chicken by Improving the Intestinal Microflora - Xu, Yunhe; Tian, Yuan; Cao, Yunfang; Li, Jianguo; Guo, Haonan; Su, Yuhong; Tian, Yumin; Wang, Cheng; Wang, Tianqi; Zhang, Lili (Frontiers in Physiology, 2019)
Lactobacillus paracasei subsp. paracasei L1 was previously isolated from sweet potato sour liquid. This bacterial species specifically binds onto starch granular surfaces, triggering the enzymatic hydrolysis of raw starch. We investigated the functional and safety properties of strain L1 in vitro to establish its probiotic potential, and analyzed its effect on growth performance and intestinal microflora of chicken in feeding experiments. The optimal growth conditions of strain L1 included low pH and high concentrations of bile salts and NaCl. Its 1-, 2-, and 24-h autoaggregation values were 15.8 ± 1.2%, 20.4 ± 2.3%, and 47.2 ± 0.8%, respectively, with the surface hydrophobicity value at 560 nm of 38.1 ± 2.7%. Further, its adhesion rate to Caco-2 cells was 22.37 ± 1.44%. Strain L1 was resistant to erythromycin and azithromycin, but sensitive to other antibiotics tested. For the feeding experiments, 240 chickens with similar weights were randomly divided into a control (C) group and strain L1 (L) group and fed for 8 weeks. Strain L1 promoted the weight gain of chickens in L group. A significant increase in the population size of the two phyla and 23 genera in the small intestine was observed in the presence of strain L1 (P < 0.05), with 0 phyla and 4 genera showing significant increase in the cecum (P < 0.05). In the small intestine, the abundance of six functional genes at Kyoto Encyclopedia of Genes and Genomes (KEGG) level 2 and 49 genes at KEGG level 3 was significantly increased in group L (P < 0.05), with lesser changes noted in the cecum. An increase in the metabolic pathway functions, including enzyme families and the digestive system, was observed in the intestinal microbiota in the L group compared to the C group. However, the other metabolic pathway functions, including metabolism of fatty acid biosynthesis, as well as metabolism of glycerolipids and propanoate, increased in the cecal microbiota of the L group relative to the C group. These changes are most likely related to the changes in the gut microbiota composition. Collectively, strain L1 supplementation may promote growth performance and improve the intestinal microflora in chicken although further studies are needed to confirm this.